The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2000
DOI: 10.1034/j.1399-3054.2000.110104.x
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a hexokinase complex is associated with changes in energy utilization in celery organs and cells

Abstract: We previously presented evidence that the hexose‐regulated repression of the mannitol catabolic enzyme mannitol dehydrogenase (MTD) in celery (Apium graveolens L.) may be mediated by hexokinase (EC 2.7.1.1) (HK) [Prata et al. (1997) Plant Physiol 114: 307–314]. To see if differential regulation of HK forms might be involved in the sugar‐regulated repression of MTD we characterized two forms of HK with respect to their expression in various plant organs as well as in celery suspension cell cultures. We found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…As previously reported (e.g., Schnarrenberger 1990;Yamamoto et al 2000), we found that HK was not only associated with mitochondria and chloroplasts, but also had a signiWcant cytosolic presence. In contrast, no HK was detected in the apoplast of either untreated or SA treated tissues (Fig.…”
Section: Mtd Is Secreted In Tobacco In Response To Salicylic Acidsupporting
confidence: 71%
“…As previously reported (e.g., Schnarrenberger 1990;Yamamoto et al 2000), we found that HK was not only associated with mitochondria and chloroplasts, but also had a signiWcant cytosolic presence. In contrast, no HK was detected in the apoplast of either untreated or SA treated tissues (Fig.…”
Section: Mtd Is Secreted In Tobacco In Response To Salicylic Acidsupporting
confidence: 71%
“…Different from studies on cytosolic enzymes, phenyl-Sepharose step was 50 times more efficient in purifying maize NC-HK 1 with similar yields ( Table 1), indicating that this is a suitable step for the purification of NC-HKs. Several studies have been performed with non-cytosolic HKs from different plants (1)(2)(3)(5)(6)(7)(8)(9)(10)(11)(12)(13)28,37). However, since these studies focused on the sub-cellular localization or the determination of the kinetic properties of these enzymes, the current study presents for the first time a procedure for the purification of particulate HKs from plants.…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical studies suggested that hexokinase isozymes diVer in their location within plant cells. Thus, hexokinases have been reported to be associated with mitochondria (Dry et al 1983;Miernyk and Dennis 1983;Tanner et al 1983;Cosio and Bustamante 1984;Schnarrenberger 1990;Galina et al 1995;Wiese et al 1999;Yamamoto et al 2000;da-Silva et al 2001;Giege et al 2003;Rolland and Sheen 2005), the Golgi complex (da-Silva et al 2001), the chloroplast stroma (Miernyk and Dennis 1983;Singh et al 1993) and the chloroplast membrane (Singh et al 1993). Yet, most of these biochemical studies were carried out without knowledge of the number or sequences of the genes encoding hexokinases and the intracellular localization of the corresponding isozymes.…”
Section: Introductionmentioning
confidence: 94%